2021
DOI: 10.1038/s41415-021-3008-x
|View full text |Cite|
|
Sign up to set email alerts
|

An investigation into possible factors that may impact on the potential for inappropriate prescriptions of antibiotics: a survey of general dental practitioners' approach to treating adults with acute dental pain

Abstract: Investigates the factors that might influence the inappropriate use of antibiotics in the management of acute dental pain before the COVID-19 pandemic.Involves an online questionnaire-based survey of UK-based GDPs.The survey collected data relating to the likelihood of antibiotics being used in two clinical scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Male dentists in the Lorraine region, with less years of practice, and having a predominant surgery practice, had the best antibiotics' prescription practices. As it has been shown for GPs [23], we can hypothesise that male dentists might have a better attendance to postgraduate training, which has a positive impact on knowledge [24,25], and thus on compliance with guidelines. But this hypothesis would need further investigation.…”
Section: Summary Of the Principal Ndingsmentioning
confidence: 86%
See 1 more Smart Citation
“…Male dentists in the Lorraine region, with less years of practice, and having a predominant surgery practice, had the best antibiotics' prescription practices. As it has been shown for GPs [23], we can hypothesise that male dentists might have a better attendance to postgraduate training, which has a positive impact on knowledge [24,25], and thus on compliance with guidelines. But this hypothesis would need further investigation.…”
Section: Summary Of the Principal Ndingsmentioning
confidence: 86%
“…The authors identi ed that the likelihood of inappropriate prescriptions was increased by the following factors: the quali cation from a non-UK university, the low or no con dence in achieving adequate local anaesthesia, the duration of the appointment (< 20 minutes versus all other times), and the lack of a postgraduate quali cation. [25] A scoping review conducted in 2018 identi ed dentist-related factors in uencing the use and the misuse of antibiotics in dentistry. [14] Some of the characteristics we identi ed in the present study were already reported in the literature: practice location, practice type, years in practice, and dentist's gender.…”
Section: Summary Of the Principal Ndingsmentioning
confidence: 99%
“…Male dentists in the Lorraine region, with less years of practice, and having a predominant surgery practice, had the best antibiotics’ prescription practices. As it has been shown for general practitioners [ 23 ], we can hypothesise that male dentists might have a better attendance to postgraduate training, which has a positive impact on knowledge [ 24 , 25 ], and thus on compliance with guidelines. But this hypothesis would need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnographic study which underpins this intervention development also suggested that it takes longer to deliver dental procedures than antibiotics during urgent dental appointments [ 11 ]. A scenario-based questionnaire study has also shown that appointments shorter than 20 min are a risk factor for inappropriate antibiotic prescribing (not in accordance with guidelines) [ 46 ]. Furthermore, the National Institute for Health and Care Excellence guideline on shared decision-making places emphasises on providing enough time for people to make the decision that’s right for them [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the first workshop, three groups of 5 or 6 stakeholders worked with flashcards to become acquainted with each of the 31 factors. The groups were also asked to identify elements of existing antimicrobial stewardship tools [ 14 , 35 , 46 , 47 , 51 ] which they would like to see translated into the new intervention for dentistry. A scribe from made a graphic (cartoon) record of the meeting, which acted to both collate ideas and stimulate discussion among the whole group about the factors and initial feelings about relative importance of each factor.…”
Section: Methodsmentioning
confidence: 99%